Odpowiedzi

2010-01-31T15:06:22+01:00
A)[(x-5)(x+3)+(2x+4)(x+1)](x+3)=
[(x2+3x-5x-15)+(2x2+2x+4x+4)](x+3)=
[(x2-2x-15)+(2x2+6x+4)](x+3)= (x2-2x-15+2x2+6x+4)(x+3)=
(3x2+4x-11)(x+3)=3x3+9x2+4x2+12x-11x-33=3x3+13x2+x-33

b) (2-x)[(x+2)(x-4)-(2x+1)(-x-3)]=(2-x)[(x2-4x+2x-8)-(-2x2-6x-x-3)]=
(2-x)[(x2-2x-8)-(-2x2-7x-3)]=(2-x)(x2-2x-8+4x2+7x+3)=
(2-x)(6x2+5x-5)=12x2-6x3+10x-5x2-10+5x=-6x3+7x2+15x-10

c) (x-3)[(3x+1)(2x-2)+(4-2x)(5x-1)]=
(x-3)[(6x2-6x+2x-2)+(20x-4-10x+2x)]=(x-3)[(6x2-4x-2+20x-4-8x)]=
(x-3)(6x2+8x-6)=6x3-18x2+8x2-18x-6x+18=6x3-10x2-24x+18

d) [(x+1)(3x-4)-(x+5)(2x-1)](x+1)=
[(3x2-4x+3x-4)-(2x2-x+10x-5)](x+1)=[(3x2-x-4)-(2x2+9x-5)](x+1)=
(3x2-x-4-2x2-9x+5)(x+1)=(x2-10x+1)(x+1)=x3+x2-10x2-10x+x+1=
x3-8x2-9x+1
9 4 9